Kajian Ekoliterasi Lingkungan: Sikap Islam Terhadap Lingkungan Karya M. Quraish Shihab Dalam Buku Islam dan Lingkungan (Perspektif Al-Quran Meyangkut Pemeliharaan Lingkungan) - Nurullah, Sururi (ECOTAS, 2024)
Damage environment couldn’t be separated from the factors of inhabitants. At this point, human as chalip in this world should be the main focus of damage environment. For make it doesn’t sustain, religion responds it with various guidance in the holy books. The guidance of Islam in the holy Quran is clearly about how to protect nature. However, the majority of Muslims do not even realize or understand it properly. Due to this existence, the book Islam & Environment (Al-Quran Perspective Concerning Environmental Care) is present as an attempt to show clarity. M. Quraish Shihab as author of this book, immediately took various verses to display, one of the most visible points consists of six verses.